Efforts To Improve Learning Outcomes Of Basic Techniques Of Pencak Silat Scrick Kicks Through Use Of Pecing Media In The Classroom VIII.A State Middle School 14 Tanralili Maros District - M Ali; muhammad rachmat Kasmad; Nukhrawi Nawir; Muh. Adnan Hudain; Mutmainnah Mutmainnah (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to improve the learning outcomes of basic pencak silat sickle kick techniques in the martial arts sport of pencak silat through the utilization of pecing media tools in class VIII.A students of SMP Negeri 14 Tanralili Maros Regency, the research used is class action research. This research method is Classroom Action Research which consists of 2 cycles and 1 pre-cycle as an initial observation. Data collection techniques using observation, namely looking for classes that have low levels of learning completeness, tests using sickle kick assessments, and documentation. The results of the research in the initial observation with a total of 32 students reached an average learning outcome of 71 with 37.50% of students completing. Cycle I learning outcomes reached an average of 76 with 53.12% of students complete. Cycle II learning outcomes reached an average of 81 with the number of students completed by 93.75%. The conclusion that the basic technique of pencak silat sickle kick with the use of pecing media can improve student learning outcomes.